Pengaruh Pemberian Kompos Granul Diperkaya Pupuk Ponska Terhadap Sifat Fisik Tanah Dan Hasil Jagung Manis Di Inceptisol - Maimuna La Habi (JURNAL BUDIDAYA PERTANIAN, 2016)
Effort to reduce the high dependence of farmers on inorganic fertilizers is adding compost as organic fertilizer. This research was conducted to develop granular-enriched compost and evaluate the effectiveness of granular-enriched compost on corn cultivation in Inceptisol. The application of granular-enriched compost was designed in a Randomized Block Design with three replicates. Treatments included 1) without fertilizers (KGES1); 2) the granular-enriched compost (8 t/ha) (KGES2); 3) recommended dosage of inorganic fertilizers such as Urea, SP-36, and KCl (KGES3); 4) inorganic fertilizer + granular-enriched compost (8 t/ha) (KGES4); 5) ½× dosage of inorganic fertilizer + granular-enriched compost (8 t/ha) (KGES5); 6) 2 × dosage of inorganic fertilizer + granular-enriched compost (8 t/ha) (KGES6); 7) ½× dosage of inorganic fertilizer + granular-enriched compost (12 t/ha) (KGES7); and 8) 2× dosage of inorganic fertilizer + granular-enriched compost (4 t/ha) (KGES8).The granular-enriched compost used in this research had characteristic such as N 2.43 %, P 0.59 %, and K 0.86 %. The results of this study showed that the yield from the granular compost treatment (KGES2) was similar to the inorganic fertilizer treatment (KGES3). Application of inorganic fertilizer combined with compost granular-enriched compost. Over doses of inorganic fertilizer treatments had no significant (P < 0.05) differences on the yield. Based on this study it could be stated that reduction to a half dose of inorganic fertilizer combined with compost granule 12 t/ha (KGES7) could give profitable yield (7.86 t/ha). This combination could possibly reduce the inorganic fertilizer; therefore, it can be used for improving the effectiveness of fertilizer application on the corn cultivation in Inceptisols.